Ocular axial length and its associations in Chinese: the Beijing Eye Study - Guo, Yin; Jonas, Jost B. (PLOS ONE, 2012)
Purpose To investigate the normative data of ocular axial length and its associations in Chinese. Method The population-based Beijing Eye Study 2011 is a cross-sectional study performed in Greater Beijing. The study included 3468 individuals (1963 (56.6%) women) with a mean age of 64.6±9.8 years (range: 50-93 years). A detailed ophthalmic and medical examination was performed. Axial length was measured by optical low-coherence reflectometry. Results Axial length measurements were available for 3159 (91.1%) study participants. Mean axial length was 23.25±1.14 mm (range: 18.96-30.88 mm). In multivariate analysis, axial length was significantly associated with the systemic parameters of higher age (P<0.001), higher body height (P = 0.003), higher level of education (P<0.001) and urban region of habitation (P<0.001), and with the ocular parameters of thicker central cornea (P = 0.001), higher corneal curvature radius (P<0.001), deeper anterior chamber (P<0.001), thicker lens (P<0.001), more myopic refractive error (P<0.001), larger pupil diameter (P = 0.018), and higher best corrected visual acuity (P<0.001). It was additionally and negatively associated with the lens vault (P<0.001). In highly myopic eyes, axial length was significantly associated with lower level of education (P = 0.008), more myopic refractive error (P<0.001), and lower best corrected visual acuity (P = 0.034). Conclusions Mean ocular axial length in the older adult population of Greater Beijing (23.25±1.14 mm) was similar to the value measured in other urban populations and was higher than in a rural Central Indian population. The association between axial length and older age may potentially be associated with a survival artifact. The association between axial length and body height agrees with the general association between anthropomorphic measures and eye globe size. The association with the level of education and urban region of habitation confirms with previous studies. In contrast in highly myopic eyes, axial length was negatively associated with educational level and best corrected visual acuity.
Gesehen am 05.07.2018